CONCEPT MAP STRATEGY TO ORGANIZE IDEAS IN WRITING EXPOSITION TEXT - Efi Kurniati; Dyah Kusumastuti (Universitas Pendidikan Mandalika, 2019)
The purpose of this research was to find out the effectiveness of concept map to organize ideas in writing exposition text. This research was conducted in one senior high school in Purwokerto in academic year 2018/2019. The population was all the eleventh grade students in that school. Researcher used two classes as control group and experimental group. This research used quasi experimental research which was done in November 2019. The instrument of collecting data was tested. The test was done twice which called pre-test and post-test. The type of the test was writing test. T-test formula was used to analyze the data. Based on the computation, t-test result was 3.535 and the t-table was 1.677 at significant level 0.05 with the degree of freedom 48. It showed that t-result was higher than t-table. Based on the research result, it can be concluded that concept map was effective to organize ideas in writing exposition text.